Terminal Deletion of Chromosome 6q - Pen-Hua Su; Jia-Yuh Chen; Suh-Jen Chen; Kai-Chi Yang (Elsevier, 2008)
Terminal deletions of chromosome 6q are rare. Clinical features associated with 6q terminal deletion syndrome include psychomotor retardation, seizures, hypotonia, short neck, and facial abnormalities, as well as various case-specific anomalies. Here, we describe a girl with 6q terminal deletion syndrome and unusually short stature. Features of previously described patients are also summarized.